DIFFRACTIVE SCATTERING OF CHARGED PARTICLES - Ismatov, E.I.; Ubaev, J.K. (Recent Contributions to Physics, 2018)
Studied the scattering of nucleons on nucleons at high energies; studied the angular dependence under the elastic scattering of hadrons. In details considered the scattering of nucleons by deuterons. Inelastic scattering cross section of protons in the nucleus 12С was presented.